Study of Training Programme for Junior Cooperative Personnel and Member Education Part II Member Education - Planning Commission (Planning Commission, 1968)
There were two sets of questionnaires, one for the peripatetic instructors and the other for the personnel who attended the secretaries/managers and the managing committee members classes. In addition, there was a schedule for the cooperative societies with which the secretaries/managers and the managing committee members were associated. The societies located in the selected districts only were relevant for the schedule and when the selected secretaries or managing committee members were connected with more than one society, the society in which the selected person was member for the longest period was taken.
Evaluation Organisation
Evaluation Organisation